2015
DOI: 10.1080/00207543.2015.1030467
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain risk management: a literature review

Abstract: Risk management plays a vital role in effectively operating supply chains in the presence of a variety of uncertainties. Over the years, many researchers have focused on supply chain risk management (SCRM) by contributing in the areas of defining, operationalizing, and mitigating risks. In this paper, we review and synthesize the extant literature in SCRM in the past decade in a comprehensive manner. The purpose of this paper is threefold. First, we present and categorize SCRM research appearing between 2003 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
901
0
71

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 1,039 publications
(983 citation statements)
references
References 236 publications
(368 reference statements)
11
901
0
71
Order By: Relevance
“…While SCRM is a vastly expanding area (Colicchia and Strozzi, 2012;Ho et al 2015), few studies have linked it with HL. McLachlin et al (2009) suggested that SCRM is important in the humanitarian context for two reasons: (a) a supply chain interruption can cause or contribute to a humanitarian crisis, and (b) humanitarian relief efforts often face multiple risks.…”
Section: "Where Is the Crisis Management Component Of [Humanitarian Omentioning
confidence: 99%
See 4 more Smart Citations
“…While SCRM is a vastly expanding area (Colicchia and Strozzi, 2012;Ho et al 2015), few studies have linked it with HL. McLachlin et al (2009) suggested that SCRM is important in the humanitarian context for two reasons: (a) a supply chain interruption can cause or contribute to a humanitarian crisis, and (b) humanitarian relief efforts often face multiple risks.…”
Section: "Where Is the Crisis Management Component Of [Humanitarian Omentioning
confidence: 99%
“…SCRM was developed for the commercial context and is concerned with assessing, mitigating, responding to and monitoring normal and abnormal risks (disruptions) (cf. Ho et al, 2015). The present paper focuses on mitigation, with the aim of providing an initial understanding of humanitarian organizations' use of supply chain strategies (SCS) to improve their logistics preparedness.…”
Section: "Where Is the Crisis Management Component Of [Humanitarian Omentioning
confidence: 99%
See 3 more Smart Citations